An endoplasmic reticulum localized acetyl-CoA transporter is required for efficient fatty acid synthesis in Toxoplasma gondii - Biyun Qin; Bolin Fan; Yazhou Li; Yidan Wang; Bang Shen; Ningbo Xia (Open Biology)
Toxoplasma gondii is an obligate intracellular parasite that can infect humans and diverse animals. Fatty acids are critical for the growth and proliferation of T. gondii, which has at least two pathways to synthesize fatty acids, including the type II de novo synthesis pathway in the apicoplast and the elongation pathway in the endoplasmic reticulum (ER). Acetyl-CoA is the key substrate for both fatty acid synthesis pathways. In the apicoplast, acetyl-CoA is mainly provided by the pyruvate dehydrogenase complex. However, how the ER acquires acetyl-CoA is not fully understood. Here, we identified a putative acetyl-CoA transporter (TgAT1) that localized to the ER of T. gondii. Deletion of TgAT1 impaired parasite growth and invasion in vitro and attenuated tachyzoite virulence in vivo. Metabolic tracing using 13C-acetate found that loss of TgAT1 reduced the incorporation of 13C into certain fatty acids, suggesting reduced activities of elongation. Truncation of AT1 was previously reported to confer resistance to the antimalarial compound GNF179 in Plasmodium falciparum. Interestingly, GNF179 had much weaker inhibitory effect on Toxoplasma than on Plasmodium. In addition, deletion of AT1 did not affect the susceptibility of Toxoplasma to GNF179, suggesting that this compound might be taken up differently or has different inhibitory mechanisms in these parasites. Together, our data show that TgAT1 has important roles for parasite growth and fatty acid synthesis, but its disruption does not confer GNF179 resistance in T. gondii.